Morphodynamic Controls for Growth and Evolution of a Rubble Coral Island - Lara Talavera; Ana Vila-Concejo; Jody M. Webster; Courtney Smith; Stephanie Duce; Thomas E. Fellowes; Tristan Salles; Daniel Harris; Jon Hill; Will Figueira; Jörg Hacker (Remote Sensing, 2021)
Rubble islands are dynamic sedimentary features present on reef platforms that evolve under a variety of morphodynamic processes and controlling mechanisms. They provide valuable inhabitable land for small island nations, critical habitat for numerous species, and are threatened by climate change. Aiming to investigate the controlling mechanisms dictating the evolution of One Tree Island (OTI), a rubble island in the Southern Great Barrier Reef, we combined different remotely-sensed data across varying timescales with wave data extracted from satellite altimetry and cyclone activity. Our findings show that (1) OTI had expanded by 7% between 1978 and 2019, (2) significant gross planform decadal adjustments were governed by the amount, intensity, proximity, and relative position of cyclones as well as El Niño Southern Oscillation (ENSO) phases, and (3) the mechanisms of island growth involve rubble spits delivering and redistributing rubble to the island through alongshore sediment transport and wave overtopping. Frequent short-term monitoring of the island and further research coupling variations in the different factors driving island change (i.e., sediment availability, reef-wave interactions, and extreme events) are needed to shed light on the future trajectory of OTI and other rubble islands under a climate change scenario.